Comparability of Company Accounts Using IFRS and US GAAP: Empirical Evidence of European and US Financial Statements - Doni, F.; Taplin, Ross; Verona, R. (Canadian Center of Science and Education, 2016)
Purpose-The main objective of this study is to provide a judgment on the comparability of financial statements prepared under IFRS and US-GAAP. We developed two research questions for evaluating comparability within Europe (IFRS) and within the US (US GAAP) and for testing whether comparability is higher or lower when the US companies are included with the European countries. Design/Methodology/Approach-The T index framework was used to summarize the level of comparability for 13 accounting items using data from 250 companies. Findings-Empirical results are mixed. Of 13 accounting items considered, international comparability is significantly lower for 7 items and significantly higher for 4 items when the US companies are included. Furthermore, comparability amongst companies using IFRS is not consistently higher or lower than comparability amongst companies using US GAAP. Practical implications-Answers to the research questions may provide useful suggestions for IASB’s current policy direction towards global accounting standards convergence, and in particular for the IASB-FASB convergence project. The results also have implications for companies or countries considering shifting to IFRS or US GAAP. Research limitations/implications-Lack of comparability within countries, rather than between countries, suggests a need to focus on reducing options within standards rather than on differences between standards or countries. Originality value-Our empirical results show that in most cases lack of comparability may be driven by options within a standard rather than by explicit differences between standards.